COLOMBIA’S DEMOGRAPHIC TRANSITION AND ITS IMPLICATIONS FOR THE SOCIAL SECURITY SYSTEM - Turchi, Boone Alexander (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2005)
COLOMBIA’S DEMOGRAPHIC TRANSITION AND ITS IMPLICATIONS FOR THE SOCIAL SECURITY SYSTEM